2021
DOI: 10.1126/sciadv.abf1586
|View full text |Cite
|
Sign up to set email alerts
|

Multiple integrated metabolic strategies allow foraminiferan protists to thrive in anoxic marine sediments

Abstract: Oceanic deoxygenation is increasingly affecting marine ecosystems; many taxa will be severely challenged, yet certain nominally aerobic foraminifera (rhizarian protists) thrive in oxygen-depleted to anoxic, sometimes sulfidic, sediments uninhabitable to most eukaryotes. Gene expression analyses of foraminifera common to severely hypoxic or anoxic sediments identified metabolic strategies used by this abundant taxon. In field-collected and laboratory-incubated samples, foraminifera expressed denitrification gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(76 citation statements)
references
References 78 publications
3
73
0
Order By: Relevance
“…This indicates benthic foraminiferal metabolism is not uniform across species. While the ability to perform denitrification and anaerobic energy metabolism are established for N. stella (4,23), we show here that N. stella of the SBB are adept at surviving anoxia, having metabolically flexible mitochondria that function in coordination with the predicted metabolism of its peroxisomes. The metabolism predicted for B. argentea suggested the capacity to digest food vacuole contents as a facultative anaerobe.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This indicates benthic foraminiferal metabolism is not uniform across species. While the ability to perform denitrification and anaerobic energy metabolism are established for N. stella (4,23), we show here that N. stella of the SBB are adept at surviving anoxia, having metabolically flexible mitochondria that function in coordination with the predicted metabolism of its peroxisomes. The metabolism predicted for B. argentea suggested the capacity to digest food vacuole contents as a facultative anaerobe.…”
Section: Discussionmentioning
confidence: 65%
“…N. stella sequesters chloroplasts (23,29,30), likely from prey, proliferates peroxisomeendoplasmic reticulum (P-ER) complexes (7), and apparently lacks food vacuoles (23). In contrast, B. argentea is abundant at the basin's flanks, rarely occurring in the most oxygendepleted conditions (9), contains solitary to small groups of peroxisomes, and exhibits evidence of digestion of chloroplasts and other organics (5).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Globobulimina genome contains a diverse gene family encoding for nitrate transporters (Nrt) (11), a finding that is consistent with the accumulation of an intracellular NO 3- storage in denitrifying rotaliids (8-10, 16). More recent studies reported the presence of those genes in at least two additional species of foraminifera and provide alternative suggestions on the nitrate reductase homolog missing from the earlier model of denitrification in foraminifera (17, 18). The rotaliids ability to respire both oxygen (O 2 ) and NO 3- marks them as facultative anaerobes that are able to thrive in both aerobic and anaerobic conditions.…”
Section: Introductionmentioning
confidence: 81%
“…It has also been suggested that foraminifera may sometimes be transported into seeps and can also occur at tze SMTZ, but they likely not live in those sediment layers permanently (Bernhard and Bowser, 1999). Foraminfiera in general have several metabolic strategies to cope with anoxic environments (Gomaa et al, 2021) of which many remain to be understudied.…”
Section: Association With Putative Methanotrophsmentioning
confidence: 99%